ANALYZING THE RELATIONSHIP BETWEEN INDUSTRIAL POLICY AND ENTREPRENEURIAL ECOSYSTEM: Received: 30th November 2023; Revised: 04th January 2024, 07th February 2024; Accepted: 12th February 2024 - Jafarov, Nasib; Nahmatova, Nargiz; Nuralizade, Ehtiman (PEOPLE: International Journal of Social Sciences, 2024)
This article discusses the importance and articulation of innovation policy from the point of view of the entrepreneurial ecosystem approach. The paper takes the form of a literature review. To this end, the authors describe the analysis of industrial policy based on the entrepreneurial ecosystem approach proposed by Stam (2018). The research finds that innovation policy plays a crucial role in a competitive entrepreneurial environment to achieve creative destruction. The Policy tries to solve the problems that hinder the interaction of the factors that make up the entrepreneurial ecosystem. Different policy tools should be developed to formulate policies for the entrepreneurial ecosystem. Additionally, successful innovation policy tools in one ecosystem could be applied in another ecosystem.